Developmental Trial of Maternity Education Control Cards - Adolfina Nilasari; Mora Claramita; Shinta Prawitasari; Lisa Soldat (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: The behavior of a pregnant woman in maintaining her health during pregnancy is influenced by her knowledge of pregnancy. The greater the knowledge of pregnant women about pregnancy, the better the attitude of pregnant women in maintaining their pregnancy. Consequently, a primary care physician who is a health manager of pregnant women needs to pay attention to this knowledge aspect. Primary care physicians should be able to quickly identify the level of knowledge of pregnant women about pregnancy and determine whether that knowledge is sufficient. For that purpose, primary care physicians need to have the right measurement instruments.Objectives: This study aimed to develop, validate and test the instruments that primary care physicians can use to identify and add to pregnant women’s level of knowledge about pregnancy.Methods: This study involved research and development of a validated instrument that consisted of several stages, namely development, validation and testing. Validation was done through two stages, specifically content validation by experts and face validation by 7 doctors. The experimental phase was a quasi-experimental research with 35 pregnant women who presented for antenatal examination at the Puskesmas Banguntapan I (Community and Primary Health Care Center). T-tests were used to determine whether there was a significant difference between the knowledge of pregnant women before and after using the Maternity Education Control Cards.Results: The validated instrument called the Maternity Education Control Card developed by primary care physicians can be used to identify and increase the level of knowledge of pregnant women about pregnancy. The Maternity Education Control Card was validated by several experts, including communication experts, obstetricians and the Maternal and Child Health Program Coordinator at Bantul Regency. Layout, style, accessibility, and feasibility were assessed by a team of validators at the Puskesmas Banguntapan I (7 doctors and 1 midwife coordinator). The data analysis showed that there was a significant difference between pre-test and post-test scores (p = 0.000). This value was not influenced by age variables, educational level, number of pregnancies nor previous antenatal care frequency, but the level of education did affect the post-test value. The duration required for education was between 9 - 20 minutes, with an average of 14.63 minutes (± 2.61). The duration required for education related to the delta of pre and post-test values. The greater the delta, the longer time required for education.Conclusions: Maternity Education Control Card has been successfully established, validated and proven to significantly increase pregnant women’s knowledge about pregnancy.